Modern Economic Development in Japan and China
XVI, 273 p.
Keywords: The contributors provide a comparative analysis of the modern economic development of Japan and China that are often explained in frameworks of East Asian developmentalism, varies of capitalism or world economic system, and explore their broader significances for the rise and global expansion of modern economy.